2014
DOI: 10.15288/jsad.2014.75.145
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations Between Alcohol Expectancies and Adolescent Alcohol Use as a Function of Childhood ADHD

Abstract: ABSTRACT. Objective: Individuals with attention-defi cit/hyperactivity disorder (ADHD) are at increased risk for experiencing alcohol-related problems. However, previous research has not examined alcohol expectancies, a widely studied risk factor for alcohol use, in this population. The current study examined mean differences in alcohol expectancies for adolescents with and without a history of childhood ADHD. The differential association between alcohol expectancies and alcohol use 1 year later as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 26 publications
5
20
1
Order By: Relevance
“…This finding is important for multiple reasons. First, it extends our prior similar findings for alcohol use expectancies (Pedersen et al, 2014) to those for marijuana, suggesting that ADHD may be associated with a decreased awareness of the subjective effects of psychoactive substances with different psychoactive profiles. These results also suggest that the dual process model offered by Stacey and Weirs (2010), in which implicit cognitive processes, as compared to explicit cognitions, are more strongly associated with substance use behaviors among individuals with executive functioning difficulties, may explain the role of marijuana expectancies for individuals with ADHD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is important for multiple reasons. First, it extends our prior similar findings for alcohol use expectancies (Pedersen et al, 2014) to those for marijuana, suggesting that ADHD may be associated with a decreased awareness of the subjective effects of psychoactive substances with different psychoactive profiles. These results also suggest that the dual process model offered by Stacey and Weirs (2010), in which implicit cognitive processes, as compared to explicit cognitions, are more strongly associated with substance use behaviors among individuals with executive functioning difficulties, may explain the role of marijuana expectancies for individuals with ADHD.…”
Section: Discussionsupporting
confidence: 80%
“…Poor insight is a well-established characteristic of many individuals with ADHD (Hoza, Pelham, Owens, & Pillow, 2002). Recent work from our group (Pedersen, Harty, Pelham, Gnagy, & Molina, 2014) found a pattern of results opposite to the Dattilo findings. Adolescents with a documented history of ADHD in childhood had lower levels of both positive and negative alcohol expectancies compared to individuals without ADHD and, consistent with the dual process model of alcohol cognition (Stacy & Wiers, 2010), negative alcohol expectancies were less related to alcohol use for individuals with, compared to individuals without, ADHD.…”
Section: Introductioncontrasting
confidence: 69%
“…This exploratory analysis also demonstrates the utility of a qualitative approach to identify perceptions that are not captured using traditional quantitative methods (Harty et al, in press; Pedersen et al, 2014). Contrary to past studies that have demonstrated nicotine (Conners et al, 1996; Levin et al, 1996; Potter & Newhouse, 2004, 2008) and ad libitum cigarette smoking (Mitchell et al, 2014) improve attention in adults with ADHD, participants with ADHD histories did not perceive improvement in such functioning when asked to reflect on their smoking in the current study.…”
Section: Discussionmentioning
confidence: 86%
“…In another prospective study of young adults with alcohol-dependent fathers, alcohol expectations mediated the relation between externalizing symptoms and alcohol use (Schuckit & Smith, 2006), indicating that SU perceptions are an important factor in maladaptive use in at-risk samples. However, despite being at-risk for various SU outcomes, individuals with ADHD endorse lower levels of expectancies about the effects of different forms of SU (Harty, Pederson, Gnagy, Pelham, & Molina, in press; Pedersen, Harty, Pelham, Gnagy, & Molina, 2014), suggesting that ADHD may be associated with decreased awareness of subjective effects of SU using traditional rating scales (Harty et al, in press). To best capture such complex perceptions of SU and emotions in those with ADHD, qualitative methodology may have utility.…”
Section: Introductionmentioning
confidence: 99%
“…Screening and diagnostic procedures have been described previously (Molina et al, 2012; Pedersen et al, 2014; Sibley et al, 2012). Briefly, participants with childhood ADHD were diagnosed with DSM-III-R or DSM-IV ADHD at the ADD Clinic, Western Psychiatric Institute and Clinic, in Pittsburgh, PA between 1987 and 1996.…”
Section: Methodsmentioning
confidence: 99%